The Development and Validation of Conceptual Knowledge Test to Evaluate Conceptual Knowledge of Physics Prospective Teachers on Electricity and Magnetism Topic (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2018)
The conceptual knowledge test is an efficient way to measure the conceptual knowledge of physics prospective teachers on electrical and magnetism topic. The employed instrument was physical questions in the form of multiple-choice options. The process of developing and validating the conceptual knowledge test consisted of 5 steps: (1) content analysis; (2) construction of multiple-choice items; (3) readability test and expert validation; (4) limited tryout; and (5) large-scale application. The instrument validation test through trials was conducted in order to obtain the data related to difficulty index, discriminating power, distractor functionality, and reliability coefficient value that was then analyzed using ITEMAN version 3.0 program. The participants were 215 physics prospective teachers of a University in Makassar city.Â The instrument validation resulted in 40 items that consisted of 26 items for electricity and 14 items for magnetism. The instrument is called Conceptual Knowledge Test-Electricity and Magnetism (CKT-EM). The value of the reliability coefficient (Î±) (Alpha Cronbach) of 0.87 indicated that the instrument of conception test on electrical and magnetism topics was valid and sufficient to measure studentsâ€™ conception on electrical and magnetism topic.